Kronik Böbrek Yetmezliğinde Serum Ürik Asit Düzeyleri - Erdem, Emre; Özdemir, Ayşe; Kaya, Coşkun; Karataş, Ahmet; Cengiz, Kuddusi (Fırat University, 2012)
Amaç: Kronik böbrek yetmezliğinde (KBY) serum ürik asit düzeyi artar. Biz çalışmamızda diyalize girmeyen evre 3-5 KBY hastaları ile hemodiyalize giren hastaların serum ürik asit düzeylerini inceledik. Ayrıca diyalize girmeyen evre 3-5 KBY hastalarında serum ürik asit düzeyi ile ilişki faktörleri araştırdık. Gereç ve Yöntem: Çalışmamız hemodiyalize giren 46, diyalize girmeyen evre 3-5 KBY olan 93, toplam 139 hasta ile yapıldı. Hastaların kan biyokimyasal değerlerine bakıldı. Vücut kitle indeksleri (VKİ) hesaplandı. Bulgular: Hemodiyalize giren hastaların ortalama serum ürik asit düzeyi 6,4 ±1,2 mg/dl, prediyaliz KBY olarak takip edilen hastaların ortalalama serum ürik asit düzeyi ise 7,3 ±1,9 mg/dl idi (p0.05). Serum ürik asit düzeyi yüksek olan hastalarımızın ortalama VKİ'leri ve bel çevreleri daha fazla idi (p

Objective: Serum uric acid levels increase in chronic kidney disease (CKD). In our study, we examined the levels of serum uric acid levels in predialysis patients with stage 3-5 CKD and patients undergoing hemodialysis. We also searched the factors related to serum uric acid levels of predialysis patients with stage 3-5 CKD. Materials and Methods: 139 patients were included in the study; 46 patients undergoing hemodialysis and 93 patients with stage 3-5 CKD who were followed without dialysis. Serum routine biochemical parameters were studied. Body mass index (BMI) were calculated. Results: Mean serum uric acid levels were 6.4 ±1.2 mg/dl and 7.3±1.9 mg/dl in hemodialysis patients and predialysis CKD patients, respectively (p0.05). In patients with higher serum uric acid levels, mean BMI and waist circumference were higher (p
Serum Uric Acid Levels in Chronic Kidney Disease